Attenuating effects of caffeic acid phenethyl ester with intralipid on hepatotoxicity of chlorpyrifos in the case of rats - Recep Dokuyucu; Ali Bilgili; Basak Hanedan; Hatice Dogan; Ahmet Dokuyucu; Muhammed Murat Celik (Medycyna Pracy, 2016)
Background: Chlorpyrifos (CPF), insecticide widely used in agriculture, may cause poisonings in the case of humans. As a result, there is a large amount of treatment research underway to focus on the possibility of chlorpyrifos induced poisonings. The aim of this study has been to evaluate the effects of caffeic acid phenethyl ester (CAPE) and intralipid (IL) on hepatotoxicity induced by chlorpyrifos in the case of rats. Material and Methods: The rats in this study were treated with CPF (10 mg/kg body weight (b.w.), orally), CAPE (10 μmol/kg b.w., intraperitoneally), IL (18.6 ml/kg b.w., orally), CPF+CAPE, CPF+IL, and CPF+CAPE+IL. The plasma total oxidant capacity (TOC), total antioxidant capacity (TAC) were measured and the oxidative stress index (OSI) was calculated. Liver histopathology and immunohistochemical staining were performed. Results: Chlorpyrifos statistically significantly decreased the TAC levels in the rats’ plasma and increased the apoptosis and the TOC and OSI levels. In the chlorpyrifos induced liver injury, CAPE and CAPE+IL significantly decreased the plasma OSI levels and the apoptosis, and significantly increased the plasma TAC levels. Conclusions: This study revealed that CAPE and CAPE+IL attenuate chlorpyrifos induced liver injuries by decreasing oxidative stress and apoptosis. Med Pr 2016;67(6):743–749